Strategies in Increasing Income in the Local Fashion Industry (Case Study of Songket Zainal Brand in Palembang City) - Yulis Amelia; Kun Budianto; Chairunnisah Putri Ayu Ningsih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze strategies in increasing income in the local fashion industry, especially in the Zainal Songket Brand in Palembang City. The fashion industry based on traditional crafts such as songket has an important role in preserving local culture as well as a source of community economy. However, increasingly fierce market competition and changes in consumer behavior require business actors to be able to implement the right strategies to increase revenue. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The informants in this study consist of business owners, employees, and consumers of the Zainal Songket Brand. Data analysis techniques are carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that the strategies applied in increasing revenue include the development of product designs that follow trends without leaving cultural values, the use of social media as a means of promotion, improving product quality, and expanding marketing networks both offline and online. In addition, participation in events or exhibitions is also an important factor in attracting consumer interest, especially tourists. The obstacles faced include dependence on tourist visits, rising prices of raw materials, and limited weaver labor. The conclusion of this study is that the right marketing strategies and product innovation can increase the revenue of the local fashion industry, although there are still some obstacles that need to be overcome. Therefore, continuous efforts are needed in business development to be able to compete in a wider market.